Effects of compression shorts on performance recovery of collegiate football players - Basconcillo, Darwin G. 1997-; Papa, Emmanuel Liberato V. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
The purpose of this study is to study the effects of compression shorts on the performance recovery of collegiate football players. Ten (10) male football players (age: 18.9 + 1.29 years) were subjected to a randomized two-group experimental study using compression shorts during recovery for the compression group (CS) and no compression for the control group (CON). Subjects were tested on three (3) separate days. Day 1 would be allotted for gathering anthropometric measurements, familiarization of test protocols, baseline testing for performance (countermovement jump, 20m. sprint test, and Illinois agility test) and RPE will also be measured on the same day. A sport-specific sprint protocol is done to induce muscle fatigue and would immediately follow the pre-testing. CS was asked to wear the shorts right after the sprint protocol for 12H while CON will go passive recovery meaning no compression shorts worn. Day 2 will be the post-testing of scores and the same performance tests will be done and RPE will also be measured for 24H post-exercise and the same intervention is done for both groups. Same procedures are done for Day 3 for 48h post-test. Repeated measures ANOVA was used to compare the scores CS and CON. A T-test was used to compare differences between time frames (Baseline-24H-28H, and Baseline-48H). Shapiro Wilks Tests of normality revealed leg power and RPE data were not normal. Repeated measures ANOVA posted no significant difference between CS and CON for speed and agility scores (p=.16, p=.924). T-tests posted no significant difference for leg power (p=.42, p=.15, p=.44), agility scores (p=.79, p=.69, p=.94), and speed (p=.44, p=.43, p=.08) across all time frames. Shapiro Wilks Test also revealed RPE scores are not normal so Wilcoxon Signed Rank Test was enforced and also revealed no significant difference (p=0.56, p=0.56, p=1). In conclusion, compression shorts have no effect on the performance recovery of collegiate football players.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Sport clothes -- Health aspects; Sports physical therapy; Sports -- Physiological aspects; Football players